Sport technique as a determinant of athletes’ personality - Piepiora, Paweł; Maśliński, Jarosław; Gumienna, Róża; Cynarski, Wojciech (Quality in Sport, 2020)
Background & Aim: In sports, three groups of sports disciplines can be distinguished depending on the way of performing movement actions: a group with a significant degree of kinematic stabilization in the structure of sports technique; a group with a significant degree of stabilization of the dynamic structure of sports technique; a group with a significant degree of variation in sports technique. This study was intended to determine whether sport technique, depending on the degree of stabilisation and variability of movement actions, is a differentiator of athletes’ personality. Method: 90 Polish athletes (men, N=90) from clubs operating in the Polish region of Lower Silesia were purposefully selected for the study as part of three samples: breakdancers (n=30), swimmers (n=30) and shotokan style karatekas (n=30). All the subjects had been considerably successful at international sport competitions. The age of the subjects ranged between 20 and 29 years. The research method chosen was the NEO-FFI Personality Inventory. The basic statistical methods used were a one-way analysis of variance and post-hoc tests. The level of significance was set as the probability of p<0.05. The statistical analysis was performed using the Statistica 13.1 program. Results: Statistically significant differences were revealed in neuroticism among all of the groups studied, in extraversion – between dancers and karatekas, in openness to experience – between dancers and karatekas and between swimmers and karatekas, and in agreeableness – between dancers and karatekas. No statistically significant differences were revealed with regard to conscientiousness. Conclusions: Sport technique is a determinant of athletes’ personality. In addition, sport technique, depending on the degree of stabilisation and variability, is a differentiator of athletes’ personality. Therefore, athletes practising different sport disciplines are characterised by different personalities.